The Main Directions of Sustainable Development of Agricultural Production - AIMURZINA, Baglan; KAMENOVA, Mazken; OMAROVA, Ainura; NURUMOV, Aldanysh; PESTUNOVA, Galina; KARIPOVA, Ainur (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018DO - 10.14505//jemt.v9.1(25).09, 2018)
This article notes that the main task of sustainable development of agricultural production in Kazakhstan is a special approach to its financial provision and financial regulation. Features of the circulation of funds in the organization of finance of agricultural enterprises which are a combination of relations with regard to the formation, distribution and use of funds, determine the search for the main sources of income of financial resources in the agricultural sector. The aim of the research is that one of the directions of sustainable development of agricultural production and adjustment of Kazakhstan's agrarian policy should be an investment development strategy based on the current situation in the agro-industrial complex of Kazakhstan. Transfer of agro industrial complex to the industrial-innovative way of development on the basis of strengthening of its material and technical base, growth of competitiveness of agricultural production assumes an increase in financing of the agro-industrial complex.